NUTRITION FOR SPORT, EXERCISE, AND HEALTH - Spano, Marie A.; Kruskall, Laura J.; Thomas, D. Travis (Human Kinetics, 2024)
Nutrition for Sport, Exercise, and Health covers the basics of nutrition for health, including the functions and daily allowances for the energy-yielding macronutrients-carbohydrate, protein, and fat-and micronutrients; nutrition in health and disease prevention; population-based nutrition considerations for training and sports; and practical information on measuring and altering body composition. The second edition has been updated to include the most up-to-date research and relevant content, including updates based on the 2020-2025 Dietary Guidelines for Americans (DGA).